The Role of Information and Communication Technology in Enhancing Akidah Akhlak Learning Outcomes: A Study in Madrasah Aliyah - Haris, Irham Abdul (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
This study explores the impact of the Information and Communication Technology (ICT) utilization on the learning outcomes in Akidah Akhlak at Madrasah Aliyah Hidayatul Mubtadiin. A quantitative approach was employed, involving 143 students and 10 teachers. Data were collected through performance assessments, teacher readiness questionnaires, student surveys on the ICT, and classroom observations regarding ICT use. The findings show a significant positive correlation between the ICT and student learning outcomes, highlighting the importance of motivation in academic success. Furthermore, teacher readiness, particularly in integrating ICT into teaching, was found to have a substantial effect on student performance. Although ICT utilization was positively correlated with student performance, the inconsistency in its application suggests a need for further teacher training and support in using digital tools. The study emphasizes the need for combining traditional pedagogical methods with modern educational technologies to optimize student learning in Islamic education.